An analysis of journalism convergence in legacy media organisations & online news start-ups - Chua, Sherwin Kim Hee (2018)
Journalism convergence scholarship has been criticized for failing to keep pace with the rapid transformations in newsrooms. Multidimensional news convergence frameworks, in particular, have been critiqued for being inadequate in explaining convergence for two reasons. Firstly, they have become outdated as journalism has been evolving at a blistering pace in tandem with advancements in communication technology. Secondly, they remain focused on large, traditional media organisations, and has neglected online news start-ups. This thesis proposes an updated multidimensional news convergence framework that includes five dimensions – business convergence; technological convergence; convergence of contents; professional convergence; and convergence with the audience – and applies it to the examination of legacy media and digital news start-ups in Singapore. Through three case studies that include one legacy newspaper (The Straits Times) and two digital news start-ups (The Middle Ground and The Online Citizen), in-depth interviews with 19 journalists, and a content analysis of 762 online news articles, this study finds that both types of organisations similarly exhibit most of the news convergence characteristics outlined by the news convergence paradigm. However, nuanced dissimilarities in each organisation have been observed. These include the manner in which resources are allocated to enhance their digital capabilities, their platform publishing strategies and work processes, and the degree to which they require their journalists to be polyvalent in journalistic skills. This study has also observed new traits of convergence that better explain current journalistic praxes in the news companies. To meet the demands of online journalism, each company has evolved new, distinct traits and practices that enhance their multimedia digital news production and distribution, such as leveraging on novel social media features – including live videos, incorporating new communication technologies in news construction, and experimenting with intra- and inter-organisation collaborative journalism.